Social representations of AIDS and their quotidian interfaces for people living with HIV Representaciones sociales del SIDA para personas que viven con HIV y sus interfaces cotidianas Representações sociais da AIDS para pessoas que vivem com HIV e suas interfaces cotidianas - Antonio Marcos Tosoli Gomes; Érika Machado Pinto Silva; Denize Cristina de Oliveira (Revista Latino-Americana de Enfermagem, 2011)
This qualitative descriptive study, guided by the Social Representations Theory, aimed to describe the content of the social representations regarding the Acquired Immunodeficiency Syndrome (AIDS) for seropositive individuals in outpatient monitoring of the public health network and to analyze the interface of the social representations of AIDS with the quotidian of the individuals living with human immunodeficiency virus (HIV), especially in the adherence to treatment process Interviews were conducted with 30 seropositive individuals and the manual content analysis technique was used. From the analysis, six categories emerged that re-translated the quotidian of seropositive people permeated by the stigma, prejudice, struggle for life and the need for the continuous use of antiretrovirals. AIDS was assimilated to chronic diseases such as diabetes, showing a trend of transformation of the social representation of AIDS, substituting the idea of death, with life. It is concluded that people living with HIV are more optimistic due to effective treatments for the control of the disease. Se trata de un estudio cualitativo descriptivo orientado por la Teoría de las Representaciones Sociales, que objetivó describir el contenido de las representaciones sociales acerca de la Síndrome de Inmunodeficiencia Adquirida (SIDA) para los usuarios seropositivos en acompañamiento de ambulatorio en la red pública de salud y analizar la interconexión de las representaciones sociales del Sida con lo cotidiano de los individuos que viven con el virus de la inmunodeficiencia humana (HIV), especialmente al proceso de adhesión al tratamiento. Se realizaron entrevistas con 30 individuos seropositivos. Se utilizó la técnica de análisis de contenido manual. Del análisis, emergieron seis categorías que tradujeron lo cotidiano de seropositivos impregnados por el estigma, prejuicio, lucha por la vida y la necesidad del uso continuo de antirretrovirales. El Sida fue comparado a enfermedades crónicas como la diabetes, evidenciando una tendencia de transformación de la representación social del Sida, substituyendo la idea de muerte, por la de vida. Se concluye que las personas que conviven con HIV están más optimistas debido a los tratamientos eficaces en el control de la enfermedad. Trata-se de estudo qualitativo descritivo, norteado pela teoria das representações sociais. Objetivou-se descrever o conteúdo das representações sociais acerca da síndrome de imunodeficiência adquirida (AIDS) para os usuários soropositivos, em acompanhamento ambulatorial da rede pública de saúde, e analisar a interface das representações sociais da AIDS com o cotidiano dos indivíduos que vivem com o vírus da imunodeficiência humana (HIV), especialmente no processo de adesão ao tratamento. Realizaram-se entrevistas com 30 indivíduos soropositivos. Utilizou-se a técnica de análise de conteúdo manual. Da análise, emergiram seis categorias que retraduziram o cotidiano de soropositivos, permeados pelo estigma, preconceito, luta pela vida e a necessidade do uso contínuo de antirretrovirais. A AIDS foi assimilada a doenças crônicas como diabetes, evidenciando tendência para transformação da representação social da AIDS, substituindo a ideia de morte, por vida. Conclui-se que as pessoas que convivem com HIV estão mais otimistas devido aos tratamentos eficazes no controle da doença.